Botanical Ecstasies: Psychoactive Plant Formulas in India and Beyond, by Matthew Clark. (22nd July 2022) - Ferrari, Fabrizio
Abstract : Botanical Ecstasies: Psychoactive Plant Formulas in India and Beyond, by Matthew Clark. London: Psychedelic Press, 2021. 69 pp. £9.99 (pb). ISBN 978191626711.